Vocabulary for the TOEFL test : - Broukal, Milada (Thomson/Peterson's, 2002)
At some point there may be a word you to not know the meaning of, and there may be no prefix or root to help you. In this case, you must look at the context of the word. The context of a work is the setting in which the word occurs in speech or in writing. Since you normally learn words by hearing or seeing them in contexts, developing this ability will help you to learn more words. The following reading include exercises for words in context. With the exception of the last three selections, these passages are lower in overrall difficulty than the reading passages you will find the TOEFL test since the aim of this book is to teach vocabulary.